Data Science Training of Customer Segmentation to Improve Business Marketing Insight for Students of SMK Negeri 1 Malang - Lalu Tri Wijaya Nata Kusuma; Indrayadi, Bambang; Sumantri, Yeni; Fanani, Angga Akbar; Putro, Wisnu Wijayanto; Azlia, Wifqi (Fakultas Teknik, Universitas Brawijaya, 2025)
In the era of digital disruption, the retail business sector faces challenges in adapting to the ever-evolving market trends. One effective way to stay competitive is through proper customer segmentation. This study aims to enhance the skills of students at SMK Negeri 1 Malang in understanding and implementing customer segmentation using data science methods, particularly the K-Means algorithm. The training was held on September 2, 2024, using demonstration methods and case study analysis. The training provided both theoretical understanding and practical skills in processing and analyzing data using the Google Colab platform. The results of the training showed that students were able to identify customer behavior patterns using customer segmentation techniques, which could be applied to more targeted marketing strategies. The use of tools like Google Colab facilitated students in understanding the data analysis process. This training is expected to help SMK Negeri 1 Malang students become better prepared for the workforce, especially in the rapidly growing fields of digital technology and data science. It is hoped that such training will continue to evolve and provide greater benefits to students and the community.